A methodology for optimization of the complementarity between small-hydropower plants and solar PV systems. (March 2016) - Kougias, Ioannis; Szabó, Sándor; Monforti-Ferrario, Fabio; Huld, Thomas; Bódis, Katalin
Abstract: Key global energy, environmental and sustainability targets are closely related to the development of Renewable Energy Sources (RES). This includes reduction of Greenhouse Gas emissions and safe energy provision in a sustainable manner. The integration of RES in the energy mix needs to overcome the technical challenges that are related to grid's operation. Therefore, there is an increasing need to explore approaches where different RES will operate under a synergetic approach. A straightforward way to achieve that is by optimizing the complementarity among RES systems both over time and spatially. The present article developed a methodology that examines the degree of time complementarity between small hydropower stations (SHPS) and adjacent solar PV systems (SPVS). The methodology builds on an optimization algorithm that associates hydrological with solar irradiation information. In particularly, the algorithm examines possible alterations on the PV system installation (azimuth, tilt) that increase the complementarity, with minor compromises in the total solar energy output. The methodology has been tested in a case study and the outcome indicated that a compromise of 10% in the solar energy output (90% threshold) may result in a significant increase of the complementarity (66.4%). Highlights: We explained and analyzed the need for increased complementarity between Renewable Energy systems. We developed a methodology that assesses the complementarity between small hydropower and solar PV systems. An optimization algorithm was developed to maximize complementarity, with small compromises in the solar energy output. The algorithm uses cloud-based information available online in PVGIS platform (developed in our Institute). In the case study the complementarity increased by 66.4%, with 10% compromise in solar energy production.